Classification of stuttering patterns by computational means - Ganeshsundaram PC; Mayadevi; Koihari GC (Journal of All India Institute of Speech and Hearing, 1970)
This paper aims at using the computer for classifying patterns of stuttering on the basis of observations of cases noted at different times under different conditions.